Proceedings 2001 International Conference on Image Processing (Cat. No.01CH37205)
DOI: 10.1109/icip.2001.958968
|View full text |Cite
|
Sign up to set email alerts
|

Optimum color spaces for skin detection

Abstract: The objective of this paper is to show that for every color space there exists an optimum skin detector scheme such that the performance of all these skin detectors schemes is the same. To that end, a theoretical proof is provided and experiments are presented which show that the separability of the skin and no skin classes is independent of the color space chosen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 9 publications
0
92
0
1
Order By: Relevance
“…Four color spaces in conjunction with histogram based skin detection methods are evaluated in [1], claiming that skin detection performance is independent of a color space transformation that is invertible. It has been shown that RGB, YCbCr and HSV have similar performance while CbCr is different since being a 'non-invertible' color transformation.…”
Section: Related Workmentioning
confidence: 99%
“…Four color spaces in conjunction with histogram based skin detection methods are evaluated in [1], claiming that skin detection performance is independent of a color space transformation that is invertible. It has been shown that RGB, YCbCr and HSV have similar performance while CbCr is different since being a 'non-invertible' color transformation.…”
Section: Related Workmentioning
confidence: 99%
“…Peu de travaux ayant été fait à ce propos (exception faite de travaux spécifiques que nous ne pouvons reprendre directement [13] [14]), nous avons développé nos propres outils afin qu'ils accordent plus d'importance aux segments de grande taille [15]. En effet, ces segments correspondent à un élément significatif de la scène et seront probablement détectés sur les deux images, prises par le système de vision stéréoscopique, conduisant ainsi à un appariement favorable.…”
Section: F Evaluationunclassified
“…Albiol et al [6] show that the performance of a skin detection algorithm is largely unaffected by the color space choice, i.e. if an optimal skin detector is designed for every color space, then the performances will be same.…”
Section: Related Workmentioning
confidence: 99%